Assessing economic and environmental efficiency of rice production systems in Southern Thailand : An application of data envelopment analysis - Kiatpathomchai, Sirirat; Justus Liebig University Giessen (My University, 2008)
Rice farming is a dominant rural economic as well as culturally important activity in southern Thailand. Rice production in this region is constrained by bio-physical and economic factors especially high costs of production and high application rates of chemical fertilizers. In addition, the actual outputs from rice production process are not only paddy rice but also the potential negative environmental effects. The flooded condition generates methane gas emission, while the excessive use of N-fertilizers causes the emission of nitrogen gases and the leaching of nitrate. In this study, therefore, the efficiency of use of all combination inputs and efficiency of use of chemical N-fertilizers as its excessive use causes the negative externalities are focused. The objectives of this study are to investigate the existing rice production systems and to assess the technical efficiency, economic efficiency, and environmental efficiency of rice production systems, then to investigate factors affecting the technical, economic and environmental efficiency of rice production systems in southern Thailand. Two-stage DEA methodology of efficiency analysis was focused. The two-stage DEA procedure began with calculating efficiency scores from input-oriented DEA model. Then these efficiency scores were used as dependent variables in the second stage by using the Tobit regression technique. The total of 247 rice farm household samples was randomly selected from the main rice farming area, the Songkhla Lake Basin. The empirical results showed that 17, 2, and 2 percent of the sample farms were on the technical, economic, and environmental efficiency frontiers, respectively and the average technical, economic, and environmental inefficiency were 14, 32, and 46 percent, respectively. Moreover, the common significant variables affecting the efficiency were soil type and rice variety. To improve the efficiency of rice farms, therefore, soil quality testing which help to improve soil quality and efficiency use of chemical fertilizers is urgent needed to implement while the research on new technologies: new suitable rice variety and new fertilizer products are considered as long-term policy implementation.

Der Reisanbau ist sowohl eine ökonomisch für den ländlichen Raum dominante als auch kulturell bedeutsame Aktivität im südlichen Thailand. Die Reisproduktion in diesem Gebiet wird dabei von biophysischen und ökonomischen Faktoren bestimmt, insbesondere von hohen Produktionskosten und hohem Einsatz an synthetischen Düngemitteln. Neben Reis ergeben sich auch potenzielle negative Umwelteffekte als Ergebnis des Produktionsprozesses. So ergeben sich durch die Flutungen Methangas-Emissionen, während der exzessive Gebrauch von N-Düngern zu Emissionen von Stickstoff-Gasen sowie Nitratauswaschungen führt. Daher untersucht diese Studie die Effizienz des Einsatzes aller Inputkombinationen sowie die Effizienz der Verwendung synthetischer N-Düngemittel, deren exzessiver Gebrauch negative externe Effekte hervorruft. Die Studie zielt auf die Untersuchung der bestehenden Systeme zur Reisproduktion ab sowie auf die Abschätzung der technischen Effizienz, der ökonomischen Effizienz und der Umwelteffizienz. Weiterhin sollen die Faktoren identifiziert werden, die die technische, ökonomische und Umwelteffizienz im südlichen Thailand beeinflussen. Dazu wird eine zweistufige DEA-Methode zur Effizienzanalyse herangezogen. Zunächst werden die efficiency scores eines Input orientierten DEA-Modells berechnet. Diese efficiency scores werden in einer zweiten Stufe als abhängige Variablen einer Tobit Regressionsschätzung verwendet. Insgesamt wurde eine Stichprobe von 247 Reis anbauenden Haushalten aus dem Songkhla Lake Basin, der Hauptanbauregion für Reis, zufällig ausgewählt. Die empirischen Ergebnisse zeigen, dass von den untersuchten Betrieben 17% auf der technischen, 2% auf der ökonomischen und 2% auf der Umwelt efficiency frontier produzieren, während die durchschnittliche technische Ineffizienz bei 14%, die ökonomische bei 32% und die Umweltineffizienz bei 46 % liegen. Darüber hinaus sind Bodenqualität und Reissorte die signifikanten Variablen, die die Effizienz beeinflussen. Zur Verbesserung der Effizienz des Reisanbaus sind daher die Qualitätsbestimmung des Bodens zu dessen Verbesserung sowie die Verbesserung der Effizienz des Einsatzes von Düngemitteln voranzutreiben. Als langfristige Politikempfehlung ergibt sich die Bereitstellung neuer Reissorten und neuer Düngeprodukte über die verstärkten Forschungs-und Entwicklungsbemühungen.
Keywords: data envelopment analysis; efficiency analysis; rice production; Thailand; ddc:630